Fasting and Postprandial Level of Lipid Profile in Cardiovascular Disease (CVD) At CCM Medical College Durg (CG) - Dr. Karansingh Chandrakar, Dr. Harish C. Sharma, Dr. B.L.Chandrakar, (International Journal of Innovative Research in Medical Science, 2017)
Purpose: - The present study examines the Fasting and Postprandial Level of Lipid Profile in Cardiovascular Disease at CCM medical college Durg. Methods: - A total number of 227 male subjects were selected at CCM Medical College Hospital Durg. 127 subjects are suffering from cardiovascular disease average range of 32 to 60 years. 100 subjects age, sex matched was selected for control group. Controls were clinically and physically normal and healthy Results: - The Fasting levels of total cholesterol, triglycerides and VLDL-C in patients of CVD are significantly higher as compared to normal healthy controls (p < 0.001). The level of Fasting HDL-C in CVD patients is lower as compared to normal healthy controls but not significantly and the LDL-C is increased significantly in CVD patients as compared to healthy controls in fasting state. Ail parameters of lipid profile is significantly higher in CVD patients than controls (p < 0.001). In our study the lipid ratios of TC: HDL-C: LDL-C: HDL-C found higher in both fasting and postprandial (table 2.1 & 2.3) state in patients with cardiovascular disease than control and also showed higher in CVD patient whereas raised in both group patients than control group patients. Conclusion: - On the basis of our study results we concluded that the monitoring and management of dyslipidemia in cardiovascular disease patients and the data suggest that assessment and treatment. Impaired lipoprotein metabolism is one of the major an etiological factors for the pathogenesis of CVD. Assessment is usually made in the fasting state but during the postprandial period the massive amount of lipid fluxes through the intra vascular compartment. Thus, the higher TG and VLDL-C and lower HDL-C levels are better indicators of CVD than the classical risk factors like total cholesterol and LDL-C supporting the hypothesis that postprandial lipoprotein metabolism and their catabolic rate play a crucial role in the development and progression of atherosclerosis.